La Esterilización Quirúrgica: ¿Que tanto saben los habitantes de una comunidad rural de Lima? - Montalván, Luis (1997)
The aim of this study was to assess the knowledge of people from a rural community regarding contraceptive methods, focused on surgical sterilization in women. This descriptive study was performed through an open-question test asking a total of 136 childbearing women and men, between October 1th and November 31th, 1998. 44,9% were male (n=61) and 55,1% female (n=75), and the mean age was 33 ± 9,87 years. 66,2% were convivients (n=90), 23,5% were married (n=32) and 10,8% were single (n=14). One hundred twenty eight (94,1%) knew at least one contraceptive method, being preservative the most reminded, followed closely by contraceptive pills. Female surgical sterilization was known by 69,9% (n=95). 9,5% (n=9) considered that surgical sterilization lead to women deceive her husbands. Natural methods were the best, as judged by the people. 3,7% considered that family planning care was a responsability for only one partner (all of them come from the lowest educational levels). We concluded that the rate of subjects who knew some kind of contraceptive method is better than the estimate for peruvian rural communities, but it is still far from the values observed in urban areas. Information about sterilization is yet so few, despite governmental programs addressed to improve their use. We suggest to enhance educational efforts in order to achieve more and better information about family planning methods.